Comparative studies of zebrafish Danio rerio lipoprotein lipase (lpl) and hepatic lipase (lipc) genes belonging to the lipase gene family: evolution and expression pattern. Issue 2 (6th June 2014) - Feng, D.; Huang, Q. Y.; Liu, K.; Zhang, S. C.; Liu, Z. H.
<x xml:space="preserve">Abstract</x> In this study, bioinformatics analysis, tissue distribution and developmental expression pattern of lipoprotein lipase (lpl) and hepatic lipase (lipc) in zebrafish Danio rerio are reported. In adult D. rerio, lpl was highly expressed in liver. This is remarkably different from the tissue expression pattern of LPL in mammals, which is not detected in the adult liver. The expression of lipc was liver specific, which is consistent with that in mammals. During embryogenesis, lpl mRNA was increased gradually in concentration from 0·5 hpf (hour post fertilization) to 6 dpf (days post fertilization), but lipc was not expressed at the early stage of the embryo until 3 dpf. In situ hybridization further displayed the expression pattern of lpl mainly restricted to the head region including cells surrounding the mouth opening, branchial arches, pectoral fin and lateral line neuromast, whereas lipc was mainly restricted to the liver and part of head regions including lens. This lays a foundation for further investigation of lpl or lipc function and evolution in fishes.